Dimensi Sosial dan Kultural Kekerasan Berdasarkan Jender di Indonesia: Dari Penjulukan ke Diskriminasi ke Kekerasan - Mely G. Tan (Antropologi Indonesia, 2003)
This article examines the social and cultural roots of gender-based violence in Indonesia. The emphasis is on social relations, particularly ethnic group relations, and on cultural practices-especially those within the family that endanger women. The author argues that there is a process which begins with labeling, followed by state-sanctioned discrimination, and that culminates in the creation of situations prone to violence. The author provides examples from various regions in Indonesia as well as from different periods in Indonesian history. She further argues that the process can be stopped with a more positive attitude towards the diversity of Indonesian society, which must be brought about by education in the home and in schools, and by legal reforms.